Transient postprandial increase in intact circulating fibroblast growth factor-21 levels after Roux-en-Y gastric bypass: a randomized controlled clinical trial - Nielsen, Mette S.; Søberg, Susanna; Schmidt, Julie B.; Chenchar, Anne; Sjödin, Anders; Gillum, Matthew P. (PeerJ, 2021)
Background Despite a consistent link between obesity and increased circulating levels of fibroblast growth factor-21 (FGF21), the effect of weight-loss interventions on FGF21 is not clear. We aimed to determine the short- and long-term effects of Roux-en-Y gastric bypass (RYGB) on intact plasma FGF21 levels and to test the hypothesis that RYGB, but not diet-induced weight loss, increases fasting and postprandial responses of FGF21. Method Twenty-eight participants with obesity followed a low-calorie diet for 11 weeks. The 28 participants were randomized to undergo RYGB surgery at week 8 (RYGB group, n = 14), or to a control group scheduled for surgery at week 12 (n = 14). Fasting levels of intact, biologically active FGF21 (amino acids 1-181) and its postprandial responses to a mixed meal were assessed at week 7 and 11, and 78 weeks (18 months) after RYGB. Results At week 11 (3 weeks after RYGB), postprandial responses of intact FGF21 were enhanced in participants undergoing surgery at week 8 (change from week 7 to 11: P = 0.02), whereas no change was found in non-operated control participants in similar negative energy balance (change from week 7 to 11: P = 0.81). However, no between-group difference was found (P = 0.27 for the group-week-time interaction). Fasting, as well as postprandial responses in intact FGF21, were unchanged 18 months after RYGB when both the RYGB and control group were collapsed together (change from week 7 to 78 weeks after RYGB: P = 0.17). Conclusion Postprandial intact FGF21 levels were enhanced acutely after RYGB whereas no signs of sustained changes were found 18 months after surgery. When comparing the acute effect of RYGB with controls in similar negative energy balance, we failed to detect any significant differences between groups, probably due to the small sample size and large inter-individual variations, especially in response to surgery.
Keywords: Fibroblast growth factor-21; Bariatric surgery; Randomized controlled trial; Diet-induced weight loss; Weight loss